Factors associated with tobacco use among Nepalese men aged 15-49 years: data from Nepal demographic and Health Survey 2016 - Gupta, Rajat Das; Jahan, Mahmuda; Hasan, Mehedi; Sutradhar, Ipsita; Sajal, Ibrahim Hossain; Haider, Shams Shabab; Joshi, Hemraj; Haider, Mohammad Rifat; Sarker, Malabika (Clinical epidemiology and global health, 2020)
Abtsract - Background - Tobacco is one of the leading causes of premature death around the world. In Nepal, tobacco kills 15,000 people every year. Men are also the primary users of tobacco. This study aimed to discern the prevalence and associated factors of tobacco use among Nepalese men aged 15-49 years. - Methods - This was a cross-sectional study. This study used data from the Nepal Demographic and Health Survey 2016. A total of 4059 study participants aged 15-49 years were included in the final analysis. The primary outcome of interest in this study was ‘tobacco use’, which was further categorized into smoked and smokeless tobacco use. Multivariable logistic regression was performed to identify determinants of tobacco use, smoking, and smokeless tobacco use. - Results - The prevalence of overall tobacco, smoked tobacco, and smokeless tobacco use were 52.3% (95% CI: 50.0-54.6), 27.3% (95% CI: 24.5-30.3), and 40.2% (95% CI: 38.0-42.4), respectively. The prevalence of tobacco use was significantly higher among the elderly, manual workers, those of lower educational status, those of lower economic status, and residents of Province No. 2. In multivariable logistic regression analysis, older age, poor education, poor economic status, and residence in the Terai region were each found to be significantly associated with tobacco use. - Conclusion - As one out of every two Nepalese men is a tobacco consumer, pertinent public health programs need to increase advocacy against tobacco use among the mass population. Tobacco control programs should also target high-risk groups when designing interventions.
Gesehen am 23.01.2026